Pemenuhan Hak Atas Pekerjaan Dan Penghidupan Yang Layak Dalam Negara Yang Mengalami Krisis Ekonomi - Kiat, Desy; Anwar, Arman; Leatemia, Wilshen (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The economic crisis that occurred in Sri Lanka was due to the accumulation of foreign debt that could not be paid, resulting in high inflation in the country. State conditions like this have had an impact on the inability of the state to meet a decent standard of living for Sri Lankan citizens and the neglect of the rights to work of Sri Lankan citizens. Which of these rights have been regulated and have been recognized and respected through the provisions contained in the International Covenant on Economic, Social and Cultural Rights (ICESCR).Purposes of the Research: To find out the arrangements regarding the fulfillment of the right to work and a decent living by the state based on the International Covenant on Economic, Social and Cultural Rights (ICESCR).Methods of the Research: This type of research is normative juridical, where the research is carried out by collecting primary, secondary and tertiary data obtained using library research. The legal material that has been collected is analyzed qualitatively which breaks it down systematically based on legal disciplines to achieve clarity of the issues to be discussed.Results of the Research: The results of this study show that the right to a decent life and the right to work have actually been regulated, respected and recognized and protected in the provisions of ICESCR article 11 paragraph 2 of the ICESCR which states that "the fundamental right of everyone to be free from hunger" ( the basic right of everyone to be free from hunger) and article 7 of the ICESCR which regulates the right of everyone to enjoy work, so that these rights must be fulfilled as a form of respect for human rights. The economic crisis that occurred in Sri Lanka which had an impact on the non-fulfillment of the rights to a decent life and the right to work is an act or an act of non-fulfillment of human rights related to these rights which in principle constitutes a violation of human rights, so that events or this situation, the Sri Lankan government in various ways or efforts continues to take strategic steps to be able to overcome the economic crisis that is currently happening in Sri Lanka.